The Impact of Multilateral Imported Cases of COVID-19 on the Epidemic Control in China (Communications in Mathematical Research, 2020)
While the spread of COVID-19 in China is under control, the pandemic is developing rapidly around the world. Due to the normal migrationof population, China is facing the high risk from imported cases. The potentialspecific medicine and vaccine are still in the process of clinical trials. Currently,controlling the impact of imported cases is the key to prevent new outbreakof COVID-19 in China. In this paper, we propose two impulsive systems todescribe the impact of multilateral imported cases of COVID-19. Based on thepublished data, we simulate and analyze the epidemic trends under differentcontrol strategies. In particular, we compare four different scenarios and showthe corresponding medical burden. The results can be useful in designing appropriate control strategy for imported cases in practice.